PURIFICATION OF CRUDE GLYCEROL USING KOH-ACTIVATED CORNCOB CARBON AND ITS UTILIZATION AS A MOISTURIZING AGENT IN LIQUID SOAP - Amalia Qurrata A’yun; Adilah Aliyatulmuna; Rosanina Kartika Santana; Felda Mufarrihati (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
The purification of crude glycerol was carried out through an antisolvent treatment process followed by adsorption. The antisolvent treatment was performed using methanol, while adsorption was conducted using corncob biomass waste. Corncob carbon was activated with 20% KOH, followed by calcination at 400°C for 2 hours. The IR spectrum of the activated carbon showed the presence of -C=C and -C-H functional groups. The diffraction pattern of the activated carbon, with peaks at 2θ ≈ 23.3° and 41.3°, indicated an amorphous structure and an imperfect crystalline graphite structure. The antisolvent treatment process involved the addition of methanol to crude glycerol at a ratio of 3:1, followed by vacuum filtration and evaporation. The adsorption process was carried out using 0.5 g of activated carbon for 75 minutes, producing glycerol with a glycerol content of 96.29%, water content of 3.21%, ash content of 6.05%, and free fatty acid content of 0.21%. These results were in accordance with SNI 06-1564-1989 concerning crude glycerol and SNI 06-2570-1992 concerning technical glycerol. The IR spectrum of glycerol showed characteristic peaks corresponding to -O-H and -C-H groups. The obtained glycerol was used as a moisturizing agent in liquid soap. The resulting liquid soap had a pH range of 5.20-5.67 and an FFA content range of 0.57-0.60, which complied with SNI 2588:2017 concerning liquid hand soap.